User Web Access Record Mining for Business Intelligence - Kamalavadhanai, D; Aarthi, N (International Journal of Computer Sciences and Engineering, 2025)
User’s access records are captured by implementing a data mining algorithm on the website. User mostly browses those products in which he is interested. This system will capture user’s browsing pattern using data mining algorithm. This system is a web application where user can view various resources on the website. User will register their profile in an exchange of a password. User will get user ID and password in order to access the system. Once the user login’s to the system user will gain access to certain resources on the website. The links to the resources on the website have been modified such that a record of information about the access would be recorded in the database when clicked. This way, data mining can be performed on a relatively clean set of access records about the users. When user clicks on certain resources on the website his access records will be captured by the system this can be achieved with the help of data mining algorithm used in this system. By using this application, product based organization will get to know the demand for certain products. This system will help organization to target right consumers. This system will help product based firms to maintain good customer relationship. Hence, a good deal of business intelligence about the users’ behavior’s, preferences and about the popularities of the resources (products) on the website can be gained